Effect of breathing relaxation on stress related to COVID-19 pandemic among older adults in nursing homes: A pre-experimental study - Yasinta Betan; Benedikta Jenau; Herliana Monika Azi Djogo; Helmi Rumbo (JKP (Jurnal Keperawatan Padjajaran), 2024)
Background: Elderly in nursing homes are facing more mental health consequences due to the COVID-19 pandemic situation. Assessment of the appropriate intervention in declining the level of stress-related to pandemic situations among institutionalized elderly is critical.